(3JSgjd fKQ GHf BLQhes - (3YHjO Hg eMeOs; (3GHf GLQhe , CHh YHO Gddg eMeO Hf eMeO Hf OGhO GdUfgGLj,J (B723 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3bGd YHjO QHg eMeO Gddg ai cd GdCehQ CMeO eUdjkG Ydi GdQShd GdefJai hBdg hUMHg hPhi GdJbi s
(3BNQgG (B:s
(3bO Je eG CJjM di Cf CfTFg ai YGe YTQjf hGda heGFg s
(3HgG JBcd ef GdCWQGas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B215s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs